Valuation of extinction parameters of anisotropic macro-seismic wave intensities - V. E. Kulchitsky (Геофизический журнал, 2014)
A method is proposed for calculating the parameters of macroseismic intensity decay of anisotropic fields. Macroseismic field are described by the model of Blake-Shebalin to the attenuation depending on the azimuth direction «epicenter-point-score». Intensity decay function is represented as a Fourier series in azimuth. The coefficients of the Fourier series are found by the least squares method. Mechanism of optimization for model assumed to real macroseismic field has been described. The proposed method is demonstrated on examples of Vrancea, the Crimea and the Black Sea earthquakes. A good agreement between the estimates obtained with the results of other methods has been demonstrated.